Economic impact of the implementation of the rural agribusiness development program (PUAP) - Eko Supeno, Risa Bilqis Febriana, (Opción, 2020)
The purpose of this study is to describe the implementation and evaluation of the benefits generated by the Rural Agribusiness Development Program (PUAP) in the area of the farming community. This study applied qualitative method, and was conducted at Bendosewu Village, Blitar. The data is taken from observation, interviews and document analysis. The results of the study revealed that the PUAP program, in particular, had more or less provided changes for the community. In conlsusion, the implementation of the PUAP program in Karya Tani Farmers Association was considered to have had an economic impact on the farming community as the target group.